Enzymatic synthesis and characterization of maltoheptaose-based sugar esters. (15th August 2019) - Nguyen, Phu Cuong; Nguyen, My Tuyen Thi; Lee, Chang-Kyu; Oh, Il-Nam; Kim, Jae-Han; Hong, Soon-Taek; Park, Jong-Tae
Highlights: This study is the first successful enzymatic synthesis of G7-based sugar ester. The solubility of G7 in organic solvents was limited except for DMSO. Ester bond was introduced at C-6 carbon of the reducing-end glucose in G7. G7-PA monoester had melting temperature (56.3 °C) lower than the free PA. G7-PA was a good emulsifier with mono-modal droplet distribution. Abstract: In this study, maltoheptaose (G7)-based sugar esters were synthesized from maltoheptaose and fatty acids (C10–C16) using a commercial lipase. With the exception of dimethyl sulfoxide (DMSO; 76.4%, w/v), G7 showed only limited solubility in organic solvents. Among the fatty acids, palmitic acid (PA) was the best substrate for G7-based ester formation. G7-PA ester was successfully synthesized as the monoester structure exclusively in 10% DMSO of t-butanol with a 22% conversion yield. NMR and enzymatic analyses of the purified monoester product revealed that the ester bond in the G7 was located at C-6 of the glucose at the reducing end. The G7-PA monoester showed the melting temperature at 56.3 °C that was 6.5 °C lower than that of the free PA and exhibited a different endothermic pattern from the free G7. The G7-PA monoester exhibited excellent emulsifier potential with more even droplet size distribution compared with the commercial sucrose esters for an oil-in-water emulsion system.